Positividade do imunomarcador FOXP3 em células T reguladoras em lesões de micose fungoide em fases clínicas iniciais e em dermatoses inflamatórias como fator auxiliar para o diagnóstico diferencial - Shibayama, Thamy Yamashita [UNESP] (2015)
Background: The homeostatic balance of the immune system is essential for clinical evolution and control of cutaneous lymphoid neoplasias and inflammatory diseases. Regarding immunological balance the role of regulatory T cells remain unclear either in mycosis fungoides or their clinical differential diagnosis like inflammatory dermatosis. Anti- FOXP3 antibody is the most specific marker of regulatory T cells. Objective: To determine and quantify regulatory T cells using anti-FOXP3 antibody in histopathological samples of early lesions of mycosis fungoides and compare it with psoriasis vulgaris, eczematous dermatitis and lichen planus by a scoring system for FOXP3 expression. Methods: Data from 77 biopsies from 64 patients, 30 cases corresponding to mycosis fungoides and 34 to inflammatory dermatosis, observed between 1999 and 2014 at the Department of Patholgy at Botucatu Medical School - Sao Paulo State University. Biopsies were reviewed and the FOXP3 labeled cells results compared according to cases or control group. Results: Intraepidermal FOXP3 positivity was significantly lower in mycosis fungoides than inflammatory dermatosis (p<0,001). Especially significant was that 90% of lichen planus cases resulted in 50% or more of epidermal lymphocytes scored FOXP3+ whereas only 10% of mycosis fungoides group have reached this level. Conclusions: Despite the majority of early lesions of mycosis fungoides diagnosis depend mainly on clinical and histopathological correlation, the statistical significance of intraepidermal FOXP3 positivity comparing with inflammatory dermatosis allow us to include this antibody to help defining the diagnosis or giving support to suspect cases morfologically dubious of mycosis fungoides